Obratnyi adres . Obratnyi adres . Return Address . Обратный адрес - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Polling on the economic and political situation in Russia; discussion of problems in education; a lawyer answers TV viewers' questions. Contributors: Dolgov, Georgii (Anchor) Опрос общественного мнения об экономической и политической ситуации в России; обсуждение проблем образования; адвокат отвечает на вопросы телезрителей. Создатели: Долгов, Георгий (Ведущий/Ведущая)